2019
DOI: 10.1111/evo.13711
|View full text |Cite
|
Sign up to set email alerts
|

The role of variation and plasticity in parental care during the adaptive radiation of three‐spine sticklebacks

Abstract: Phenotypic plasticity might influence evolutionary processes such as adaptive radiations. Plasticity in parental care might be especially effective in facilitating adaptive radiations if it allows populations to persist in novel environments. Here, we test the hypothesis that behavioral plasticity by parents in response to predation risk facilitated the adaptive radiation of three‐spine sticklebacks. We compared the behavior of fathers across multiple ancestral (marine) and derived (freshwater) stickleback pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 63 publications
(107 reference statements)
2
8
0
Order By: Relevance
“…Instead, these shifts in variance likely result from differences among fathers in how they responded to the net treatment. This is consistent with previous results in sticklebacks that found that fathers who encountered a novel predator showed a more variable changes in paternal care behaviors relative to fathers who encountered a native predator, who showed consistent directional changes in behavior [44].…”
Section: Discussionsupporting
confidence: 92%
“…Instead, these shifts in variance likely result from differences among fathers in how they responded to the net treatment. This is consistent with previous results in sticklebacks that found that fathers who encountered a novel predator showed a more variable changes in paternal care behaviors relative to fathers who encountered a native predator, who showed consistent directional changes in behavior [44].…”
Section: Discussionsupporting
confidence: 92%
“…Shrinking and expansion of suitable habitat during glacial periods, such as expansion of the rain forests towards Cerrado and Chaco (Sobral-Souza et al 2015;Bartoleti et al 2017;Trujillo-Arias et al 2017) may have contributed to the structuring observed in the mitochondrial dataset and may have selected for individuals expressing plasticity in GPC. The results agree with the "plasticity first" hypothesis (Levis and Pfennig 2016) which postulates that while ancestral populations are expected to be plastic, these plastic responses might become genetically accommodated or assimilated in derived populations (Stein and Bell 2019). That is, there is a change in the extent of plasticity due to a shift in the environment.…”
Section: Discussionsupporting
confidence: 87%
“…This lower than expected impact of prenatal risk environments on parental care intensity may result from us using a P. promelas population that has been kept in the laboratory dating back to 1985, and possibly earlier (see Additional file 1 : Section 1 for more detail). Such laboratory populations may not have evolved predator-induced plasticity in parental care intensity due to the absence of fluctuating risk [sensu 64 ]. Consequently, risk-induced differences in parental care intensity are unlikely to be the main mechanism for the transmission of risk information across generations.…”
Section: Discussionmentioning
confidence: 99%